Karakterisasi Hidrogeologi Daerah Sekitar Tapak PLTN di Bengkayang, Kalimantan Barat - Muhammad, Adi Gunawan; Fauzi, Rachman; Karunianto, Adhika Junara; Cakrabuana, Wira; Widodo (BRIN Publishing, 2021)
Site evaluation is an important phase of site selection for commercial-scale nuclear power plants (NPP) in Indonesia. Geotechnical and radioactive material dispersion aspects are some of the aspects which are assessed in site evaluation under provisions of laws and regulations. To support those aspect evaluations, it is necessary to conduct hydrogeological characterization in the vicinity of the NPP site. The purpose of this study is to determine the hydrogeological characteristic of the vicinity of the NPP site in Bengkayang Regency, West Kalimantan Province based on geological and geophysical aspects. The methods of this study consist of geomorphological mapping, geological mapping, hydrogeological mapping, geoelectric measurement, and integrated analysis. The study area consists of three morphological units: alluvial plain, isolated hills, and coastal plain. Stratigraphically, the lithology units of the study area, from the oldest to the youngest, consist of andesite, granodiorite, diorite, quartz sand deposits, coastal deposits, and alluvial deposits. The geophysical measurement used is the geoelectric method which is conducted at 12 electrode arrays with 470 m length and spacing of 10 m. In the geoelectrical section, it can be seen that several anomalies can be interpreted as the fractured body of igneous rocks or the diorite intrusion in andesite. These anomaly values are ranged from 300 Wm to >8000 Wm. The relatively low resistivity values (<30 Wm) are interpreted as water saturated-alluvial deposits that could have a thickness of ±100 m. There are three hydrogeological units in the study area: aquifers in which flow is intergranular with high permeability, aquifers in which flow is intergranular with moderate permeability, and aquifug of local importance. Generally, the groundwater in the study area flows from SSW to NNE.